Análisis del uso de las TIC en el proceso de enseñanza aprendizaje en el área de Lenguaje y Comunicación de: octavo, noveno y décimo año de educación básica de los colegios fiscales de la ciudad de Riobamba - Chacaguasay Cepeda, Olmedo (2016)
This research aims to analyze the use of ICT in the teaching-learning process in the area of ​​Language and Communication students of eighth, ninth and tenth year of basic education in state schools in the city of Riobamba. Ignorance of the different technological resources that can be used in the classroom, causing improper use of ICT in the educational process for the realization of this research was necessary to conduct a preliminary study to discover the reality of the use of ICT as pedagogical tool in the study area, following the analysis of the impact of ICT on student learning culminated in the study of tic most used and benefits in education. This research provides a useful, comprehensive and modern knowledge about ICT, whose main benefit is to improve the teaching-learning process in the area of ​​language and communication.